Properties of Garnet Monolayer Graphene Depolarizer - Xinbing Jiao; Yangfan Shen; Xinwei Zhao; Jing Wen (IEEE Photonics Journal, 2017)
A garnet monolayer graphene depolarizer is prepared by chemical vapor deposition (CVD). The characterizations of graphene on garnet are distinguished by Raman spectroscopy and Atomic Force Microscope (AFM). The z-scanning polarization properties of an input linearly polarized beam are measured by Stokes polarimeter, which passes through the garnet monolayer graphene depolarizer. The results show that the garnet monolayer graphene depolarizes the polarized beam into similar natural light and the degree of polarization of the input linearly polarized beam can be reduced from 100% to 0.1%, while the garnet and garnet with bilayer graphene cannot depolarize the polarized light. This work presents an interesting result on depolarization effect based on graphene when a laser beam passes through in perpendicular direction of graphene.